Preserving Debt Sustainability in Low-Income Countries in the Wake of the Global Crisis. (Policy Papers; Policy Paper ;, 2010)
We cannot allow the return of economic stability to signify a return to "business as usual" for the IMF. The crisis exposed huge cracks in the international financial architecture of which the Fund is a key part. We have an historic responsibility to fix them. I urge all of us to recommit to seeing our collective goals to the finish line before reform fatigue sets inches.